In Hospital Complications of Atrial Septal Defect Device Closure at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Acharya, Kiran Prasad; Bogati, Amrit; Dhungel, Sachin; Shrestha, Manish (Journal of Nepal Health Research Council, 2020)
Background: Atrial deptal defect device closure has become the preferred method in the treatment of atrial septal defect. We aim to study the in-hospital complications of atrial septal defect device closure procedure. Methods: It was a single center, retrospective study conducted from Febuary 2016 to January 2019. Cardiac catheterization laboratory records of all consecutive patients who underwent atrial septal defect device closure was included and the in-hospital complications were been retrospectively reviewed. Results: During the study period, a total of 566 patients were attempted for device closure. In 557 (98.4%) of cases device was implanted. Among the 557 patient in which device was implanted 401(71.9%) were female. Age ranged from 5 years to 72 years with the mean of 30.9 years. Transient ST segment elevation 15 (2.6 %)was the commonest complication followed by pericardial tamponade 4 (0.7%), and cardiac arrhythmias 3 (0.5%). Conclusions: Atrial deptal defect device closure can be done safely with a high success rate and a low complication rate. Keywords: Amplatzer duct occluder; atrial septal defects; in hospital complications; transcatheter device closure.